Sociology in the Philippine setting : a modular approach - Hunt, Chester L.; Espiritu, Socorro C.; Quisumbing, Lourders R.; Green, Justing (Quezon City : SIBS Publishing House, Inc., 1998)
This is the fifth edition of Sociology in the Philippine Setting. It was first written by sociologists from the University of the Philippines in an effort to produce a text for college students of sociology.
CHAPTER 1. The Role and Scope of Sociology -- 2. The Nature and role of group behavior -- 3. Culture and behavior -- 4. Socialization, Conformity and Deviance -- 5. Social Processes -- 6. Philippine Values -- 7. Communication, Social Movements, and collective behavior -- 8. Social Class -- 9. Age, Sex, and Ethnicity -- 10. Institutions -- 11.The family -- 12. Religion and Society -- 13. The Rural Community -- 14. The Urban community -- 15. Population Growth and distribution -- 16. Social Change.
Includes index.
Keywords: SOCIOLOGY